The long path to pregnancy: early experience with dual anonymous gamete donation in a European in vitro fertilisation referral centre - Sills Eric; Mykhaylyshyn Lyubov O; Dorofeyeva Ulyana S; Walsh David J; Salma Umme; Omar Ahmed B; Coull Graham D; David Ileana A; Brickell Kathy M; Tsar Olga M; Walsh Anthony PH (BMC, 2010)
Abstract Background This investigation describes features of patients undergoing in vitro fertilisation (IVF) and embryo transfer (ET) where both gametes were obtained from anonymous donors. Methods Gamete unsuitability or loss was confirmed in both members of seven otherwise healthy couples presenting for reproductive endocrinology consultation over a 12-month interval in Ireland. IVF was undertaken with fresh oocytes provided by anonymous donors in Ukraine; frozen sperm (anonymous donor) was obtained from a licensed tissue establishment. For recipients, saline-enhanced sonography was used to assess intrauterine contour with endometrial preparation via transdermal estrogen. Results Among commissioning couples, mean±SD female and male age was 41.9 ± 3.7 and 44.6 ± 3.5 yrs, respectively. During this period, female age for non dual anonymous gamete donation IVF patients was 37.9 ± 3 yrs (p < 0.001). Infertility duration was ≥3 yrs for couples enrolling in dual gamete donation, and each had ≥2 prior failed fertility treatments using native oocytes. All seven recipient couples proceeded to embryo transfer, although one patient had two transfers. Clinical pregnancy was achieved for 5/7 (71.4%) patients. Non-transferred cryopreserved embryos were available for all seven couples. Conclusions Mean age of females undergoing dual anonymous donor gamete donation with IVF is significantly higher than the background IVF patient population. Even when neither partner is able to contribute any gametes for IVF, the clinical pregnancy rate per transfer can be satisfactory if both anonymous egg and sperm donation are used concurrently. Our report emphasises the role of pre-treatment counselling in dual anonymous gamete donation, and presents a coordinated screening and treatment approach in IVF where this option may be contemplated.